Death and the librarian - Gilbert, Victoria (Gilbert, Victoria. Blue Ridge library mystery, 2025)
"When a woman is murdered after accusing art dealer Kurt Kendrick of a cold case crime, librarian Amy Muir races to uncover the truth and protect her family"--